Macrophage IL-1β-positive microvesicles exhibit thrombo-inflammatory properties and are detectable in patients with active juvenile idiopathic arthritis - Cambon, Audrey; Rebelle, Charlotte; Bachelier, Richard; Arnaud, Laurent; Robert, Stéphane; Lagarde, Marie; Muller, Romain; Tellier, Edwige; Kara, Yéter; Leroyer, Aurélie; Farnarier, Catherine; Vallier, Loris; et al. (Frontiers in Immunology, 2023)
Objective. IL-1 is a leaderless cytokine with poorly known secretory mechanisms which is barely detectable in serum of patients, including those with an IL-1-mediated disease such as systemic-Juvenile Idiopathic Arthritis (sJIA). Leukocyte microvesicles (MV) may be a mechanism of IL-1 secretion. The first objective of our study was to characterized IL-1β-positive MV obtained from macrophage cell culture supernatants and to investigate their biological functions in vitro and in vivo. The second objective was to detect circulating IL-1β-positive MV in JIA patients.Methods. MV were purified by serial centrifugations from PBMCs, or THP-1 differentiated into macrophages, then stimulated with LPS +/-ATP. MV content was analyzed for the presence of IL-1ß, NLRP3 inflammasome, caspase-1, P2X7 receptor and tissue factor (TF) using ELISA, western blot or flow cytometry. MV biological properties were studied in vitro by measuring VCAM-1, ICAM-1 and E-selectin expression after HUVEC co-culture and factor-Xa generation test was realized. In vivo, MV ability to recruit leukocytes in a murine model of peritonitis was evaluated. Plasmatic IL-1β-positive MV were studied ex vivo in 10 active JIA patients using flow cytometry.Results. THP-1-derived macrophages stimulated with LPS and ATP released MV which contained NLRP3, caspase-1, the 33kDa precursor and 17kDa mature forms of IL-1 and bioactive TF. IL-1positive MV expressed P2X7 receptor and released soluble IL-1 in response to ATP stimulation in vitro. In mice, MV induced a leukocytes peritoneal infiltrate which was reduced by treatment with IL-1 receptor antagonist. Finally, IL-1β-positive MV were detectable in plasma from 10 active JIA patients.MV shed from activated macrophages contain IL-1β, NLRP3 inflammasome components and TF, and constitute thrombo-inflammatory vectors that can be detected in the plasma from active JIA patients.